Tarifa socialmente justa para el servicio de transporte público urbano y su relación con los tiempos de recorrido e intervalos de despacho - Jaramillo Sangurima, Wilson Eduardo (2017)
Define a socially fair rate for public transportation is an important issue that concerns the authorities to regulate the mobility in cities. In the present investigation the relationship between the speed of vehicle travel with the value of rate necessary to achieve the balance between revenue and expenditure. The research method employed includes the analysis of various operating scenarios. For the analysis of each scenario is used as the ITP software tool, which generates information that allows the calculation of the rate using the methodology defined by the ANT – Ecuador. The procedures used for the development of research can be replicated in all kinds of routes andany city, finally concluding that the higher the travel speed, the lower the operating costs of the route.